PENGARUH PERANAN AUDIT INTERNAL TERHADAP PENERAPAN GOOD CORPORATE GOVERNANCE PT PUPUK KALIMANTAN TIMUR BONTANG - Sailawati Sailawati; Muhammad Suyudi; Gina Selviana (Politeknik Negeri Samarinda, 2021)
This study aims to determine the effect of the role of internal audit on the implementation of good corporate governance at PT Pupuk Kalimantan Timur Bontang. This research used questionnaires to collect primary data. The data quality testing was done by using the validity test and reliability test. Normality test, multicollinearity test and heteroscedasticity test were used for the statistical test. The hypothesis testing examined by the simple regression analysis, t-test and correlation coefficients. Based on the results, the alternative hypothesis (Ha) is accepted. The result of this study indicates that the role of internal audit has a significant effect on the implementation of good corporate governance at PT Pupuk Kalimantan Timur Bontang, indicated by the significance value < 0.05 and tcount > ttable. This result at the same time shows similarities with the previous studies, namely, Putra (2014) and Lubis (2017).Keywords: Internal Audit, Good Corporate Governance.